Arbuscular Mycorrhizal Fungal Associations with Ricinus communis L. in Dharashiv District - Sarwade, Prakash; Gaisamudre (Sarwade) , Kavita N.; Gaikwad, Rajesh S. (Plantae Scientia, 2024)
An examination of the Arbuscular mycorrhizal (AM) associations in Ricinus communis L. plants was conducted across various locations in Maharashtra's Dharashiv district. The findings revealed that R. communis L. plants at all sites exhibited AM fungal root colonization and spore presence in the surrounding soil. The highest percentage of AM fungal root colonization was found in Paranda (98%), while Omerga showed the lowest at 65%. Spore density was highest in Paranda (345) and lowest in Kallam (104). Five AM fungal genera were identified, with Acaulospora spp. and Glomus spp. being predominant, while Sclerocystis spp. and Gigaspora spp. were less common.